Production of chain-extended cinnamoyl compounds by overexpressing two adjacent cluster-situated LuxR regulators in Streptomyces globisporus C-1027 - Li, Xingxing; Ren, Weicong; Li, Yihong; Shi, Yuanyuan; Sun, Hongmin; Wang, Lifei; Wu, Linzhuan; Xie, Yunying; Du, Yu; Jiang, Zhibo; Hong, Bin (Frontiers in Microbiology, 2022)
Natural products from microorganisms are important sources for drug discovery. With the development of high-throughput sequencing technology and bioinformatics, a large amount of uncharacterized biosynthetic gene clusters (BGCs) in microorganisms have been found, which show the potential for novel natural product production. Nine BGCs containing PKS and/or NRPS in Streptomyces globisporus C-1027 were transcriptionally low/silent under the experimental fermentation conditions, and the products of these clusters are unknown. Thus, we tried to activate these BGCs to explore cryptic products of this strain. We constructed the cluster-situated regulator over-expressing strains which contained regulator gene(s) under the control of the constitutive promoter ermE*p in S. globisporus C-1027. Overexpression of regulators in cluster 26 resulted in significant transcriptional upregulation of biosynthetic genes. With the separation and identification of products from the over-expressing strain OELuxR1R2, three ortho-methyl phenyl alkenoic acids (compounds 1-3) were obtained. Gene disruption showed that compounds 1 and 2 were completely abolished in the mutant GlaEKO, but were hardly affected by deletion of the genes orf3 or echA in cluster 26. The type II PKS biosynthetic pathway of chain-extended cinnamoyl compounds was deduced by bioinformatics analysis. This study showed that overexpression of two adjacent cluster-situated LuxR regulator(s) is an effective strategy to connect the orphan BGC to its products.